Heterogeneous Wettability Surfaces: Principle, Construction, and Applications. Issue 2 (13th September 2020) - Li, Huizeng; Li, An; Zhao, Zhipeng; Li, Mingzhu; Song, Yanlin
Abstract : A functional substrate with heterogeneous wettability elaborately integrates the water loving and repellent properties onto an individual surface. Compared with homogeneous surfaces, nonuniformity in wettability endows a heterogeneous surface with a more remarkable capability for manipulation of the solid–liquid–gas interactions, which contributes to the progress and innovation in various applications, such as device fabrication, biological screening, and sample analysis. Recently, the development in microfabrication techniques has greatly promoted the versatility and diversity in the design and fabrication of substrates with high‐precision and high‐resolution heterogeneous wettability. In this review, the general principle of liquid manipulation using heterogeneous wettability surfaces is discussed. Then, the construction methodology of substrates with heterogeneous wettability surfaces is outlined in the order of chemical modification and physical engineering. Typical applications focused on optic/electronic device fabrication and biosensing/detection are summarized. Finally, current challenges and research prospects to enhance the practicality and universality of heterogeneous wettability substrates are also proposed. Abstract : A heterogeneous wettability substrate elaborately combines hydrophilic and hydrophobic properties onto an individual surface. Compared with homogeneous substrates, heterogeneous wettability endows surfaces with the capability for more accurate and sophisticated manipulation of solid–liquid–gas interactions. In this review, the recent progress in heterogeneous wettability fabrication techniques and typical applications focusing on optic/electronic device fabrication and biosensing/detection are systematically summarized.